New Insight into the Structural Model in Southern Sumatra Indonesia using Gravity and Magnetic Data: Implications for Geothermal Resources (Rudarsko-geološko-naftni zbornik, 2025)
The island of Sumatra was formed through complex tectonic processes that produce a variety of geological resources, including geothermal potential. Fault structures, particularly the Great Sumatran Fault (GSF), which are associated with surface geothermal manifestations. This study aims to comprehensively evaluate the geothermal potential in southern Sumatra using a combination of gravity and magnetic data.. The results show that the heat source in Sumatra is intrusive volcanic rocks with a density of 2.8 g/cm³ and a susceptibility value of 0.007, extending from west to south in a northwest-southeast pattern. These rocks are part of the Kikim Formation (Tpok) from the magma residue of Mount Bukit Besar, Bukit Lumut, and Bukit Balai, at a depth of more than 7 km. The reservoir layer in the center is likely caused by the SumThe island of Sumatra was formed through complex tectonic processes that produce a variety of geological resources, including geothermal potential. Fault structures, particularly the Great Sumatran Fault (GSF), are associated with surface geothermal manifestations. The objective of this investigation is to conduct a thorough assessment of the geothermal potential in southern Sumatra by utilising a combination of magnetic and gravity data. The results show that the heat source in Sumatra is intrusive volcanic rocks with a density of 2.8 g/cm³ and a susceptibility value of 0.007, extending from west to south in a northwest-southeast pattern. These rocks are part of the Kikim Formation (Tpok) from the magma residue of Mount Bukit Besar, Bukit Lumut, and Bukit Balai, at a depth of more than 7 km. The reservoir layer in the center is likely caused by the Sumatra Fault fracture zone or sedimentary rocks, consisting of the Hulusimpang and Gumai formations, with a density of 2.6 g/cm³ and a susceptibility of 0.075 at a depth of 1000–1500 m. The heat flow ranges from 55.1 to 79 mW/m², and the geothermal gradient is between 21.1 and 31.6°C/km. Another finding is the high geothermal gradient observed beneath volcanic complexes, including the Bukit Barisan Mountains area. The northwest-southeast fault structure parallel to the GSF suggests that this fault controls the geothermal system in Sumatra, providing new insight into the fault control mechanism of the geothermal system. The integration of gravity and magnetic data reveals new relationships between tectonic structures in the GSF zone and previously unexplored geothermal potential.